Role of Religiosity in Moderating Factors Affecting Customer's Preference to Choose Financing - Setiawan, Fery; Pristi A., Eka Destriyanto; Purwaningsih, Titis (Jurnal Samudra Ekonomi dan Bisnis, 2023)
This study aims to examine the factor of religiosity as a moderator variable between the influence of production factors and economic potential on customer preferences in choosing to finance. The object is the customer of Baitul Mal Wat Tamwil (BMT) Khasanah Jabung Ponorogo, who has used financing products at such Islamic financial institutions. Quantitative methods are used to analyze the data, assisted by the Smart PLS application program. The result of this study indicates that religiosity strengthens the variables of product factors and economic potential in influencing customer preferences to choose to finance. Therefore, it is concluded that customers understand the benefits and blessings that will be obtained if you choose a sharia financial institution, which here is BMT Khasanah, as a partner in running its business.